298 Antenatal Taurine Supplementation Reduces Cerebral Cell Apoptosis in Fetal Rats with Intrauterine Growth Restriction. (October 2012) - Liu, J; Wang, XF; Teng, HY; Yang, N; Ren, XT
Abstract : Intrauterine growth restriction (IUGR) is closely associated with neonatal and prenatal morbidity, mortality and even with adult diseases. Term infants with IUGR have a five- to seven-fold risk of developing cerebral palsy, compared with gestational age-matched infants with normal birth weights. Our previous study showed that antenatal supplementation of taurine can improve brain ultrastructure of fetal rats with IUGR, but the mechanism remains unclear. This paper was to explore the effect of antenatal taurine supplementation on cerebral apoptosis and glial cell line-derived neurotrophic factor (GDNF)-cysteinyl aspartate specific (caspase-3) in fetal rats with IUGR. Fifteen pregnant rats were randomly divided into 3 groups: control group, IUGR and IUGR+antenatal taurine supplements. Taurine was added to the diet of the taurine group at a dose of 300 mg/kg·d from 12 days after conception until natural delivery. Two fetal rats were chosen in every litter. brain cellular apoptosis was detected using TUNEL, and the changes in protein expression of GDNF and caspase-3 using immunohistochemistry. The results showed that (1)the counts of apoptotic brain cells in the control group, IUGR group and IUGR with antenatal taurine supplementation group were (0.28±0.57)%, (15.30±5.96)%, (9.36±3.92)%, respectively. (2) The expressions of GDNF in three groups respectively were (93.56±6.73), (120.36±6.23) and (139.56± 5.28) (F= 492.56). (3) The expressions of caspase-3 in three groups respectively were (7.51± 2.31), (151.33±24.41) and (37.29±11.27)(F=128.18. Antenatal taurine can significantly decrease brain apoptosis, the mechanism maybe through increasing the expression of GDNF and decreasing the expression of caspase-3. This work was supported by Natural Science Foundation of China (81170577).